Arbeit zur falschen Zeit am falschen Platz? Eine Matching-Analyse zu gesundheitlichen Beanspruchungen bei Schicht- und Nachtarbeit - Olaf Struck; Matthias Dütsch; Verena Liebig; Angelina Springer (Journal for Labour Market Research, 2014)
– Many studies report diseases caused by shift and night work. As a rule, however, such studies do not take into account socio-demographic factors and job characteristics. Based on the BIBB/BAuA Employment Survey 2006, the present paper looks into the effects of various job-specific and socio-structural factors on physical and mental health as well as sleeping disorders. The analysis was carried out using the matching approach. Furthermore, the matching approach was used to form to shift and night work groups as structurally identical references as possible with regard to social-structural characteristics and job features. This strategy makes it possible to extract independent effects of the timing of work on health problems. The result: The question as to whether people work at physically, socially or psychologically strenuous workplaces is essential for their health stresses. It is slightly less important whether this work is done in the daytime or at night.
Keywords: 330; Schichtarbeit; Nachtarbeit; Gesundheitsgefährdung; Arbeitsbelastung; medizinische Faktoren; BIBB/BAuA-Erhebung; psychische Faktoren; Schlaf; Schichtarbeitnehmer